Experimental investigation of flows in a high-head pump-turbine draft tube at turbine mode. (July 2018) - Lai, X D; Liang, Q W; Chen, X M; Gou, Q Q; Ye, D X; Xia, M M
Abstract: The accurate prediction of flow patterns is essential during the optimization design of a pump-turbine. To determine the flow patterns and validate the flow simulation inside a pump-turbine, Laser Doppler Velocimetry (LDV) measurements and 3D flow simulation in the draft tube cone of a high-head pump-turbine model have been performed at normal operating conditions in turbine and pump modes. Velocity distributions were measured for operating conditions covering the speed factor n ED =0.21 and 0.19 at turbine mode for loads ranging from 40% to 100% the rated power as well as best efficiency point. Measurements of unsteady flows inside the draft tube cone were conducted at a high precision hydraulic model test rig with LDV system from TSI Co. The 3D flows through the pump-turbine model were numerically simulated with ANSYS/CFX ® software at all the measured operating points. Both measured and simulated velocity profiles are presented and analyzed to show the influence of operating parameters on the velocity and swirl characteristics in draft tube inlet. Comparison of the measurement and simulation shows rather good agreement at the best efficiency point and full load but clear discrepancies at part load. The experiment data such as the velocity profiles, pressure signals, and amplitude and frequency characteristics of the instantaneous tangential velocity at various loads offers the possibility to assess the precision in performance prediction in the pump-turbine using the numerical simulation methods. The measured instantaneous tangential velocity at part loads reveals a periodic peak, which is asynchronous to that of runner's rotating speed and can be used to determine the characteristic frequency of rotating vortex rope at part loads. Axial and tangential velocity fields obtained from LDV measurements at normal operating points can be used to validate the numerical simulation in optimization design.